Characteristics and controlling factors of reservoir space of mudstone and shale in Es3x in the Zhanhua Sag. (December 2017) - Ning, Chuanxiang; Jiang, Zhenxue; Gao, Zhiye; Su, Siyuan; Li, Tingwei; Wang, Guozhen; Wang, Zhi; Li, Zheng; Zhu, Rifang; Chen, Lei
Abstract: Zhanhua Sag is a widely accepted target zone with huge exploration and development potential for shale oil and shale gas resources. Many detailed studies have been undertaken around the geochemistry of the lower section of the third member of the Shahejie Formation (Es3x), while few studies have focused on the reservoir. In this study, based on the mineralogical features and geochemical characteristics, and by using statistical methods, the characteristics and controlling factors of reservoir space of mudstone and shale in Es3x in the Zhanhua Sag are explored through field-emission scanning electron microscopy (FE-SEM), high pressure mercury injection capillary pressure (MICP), and nuclear magnetic resonance (NMR) techniques. Three major findings were obtained. ① There are micropores and microfractures in the reservoir space, which include intergranular pores, clay intercrystal pores, pyrite intercrystal pores, dissolved pores, structural microfractures, and bedding microfractures. ② According to the features of pore size distribution (PSD), the pore distribution can be divided into the following three categories: 0–50 nm, 50 nm–2 μm, and >2 μm; the average volumes of these components are 0.01079 mL g −1, 0.00361 mL g −1, and 0.00355 mL g −1, respectively, thus showing that the pores whose radii are distributed at 0–50 nm form the most important reservoir space (though those with the 50 nm–2 μm and >2 μm radii are also important and cannot be ignored). ③ There are different controlling factors when it comes to different scale pores. Based on statistics and FE-SEM results, the dissolved pores in calcite were determined to be the controlling factor for the 0–50 nm portion, the intercrystalline pores in clay and pyrite, and intergranular pores between authigenic minerals (calcite, dolomite, and pyrite) and clastic minerals (calcite and dolomite) were determined to be the controlling factors for the 50 nm–2 μm portion, and the structural microfractures and bedding microfractures were determined to be the main factors for the >2 μm portion. Furthermore, it is the brittle minerals content and bedded structure that control the microfractures. This study thus clarifies the types and characteristics of reservoir space and identifies pore structure controlling factors of mudstone and shale in Es3x in the Zhanhua Sag; this information has important significance for future reservoir evaluations. Highlights: Intergranular pores, intercrystalline pores, and dissolved pores are the dominate pore types. The 50 nm and 2 μm were taken as the boundaries to divide the PSD based on the actual data. The controlling factors of different scale spaces were determined based on correlation analysis and observations.